Evaluating the Effect of Mat Pilates on Pain and Functional Outcomes in Patients with Knee Osteoarthritis - Deshpande, Shatakshi; Pal, Renuka; Aggarwal, Kapil; Khan, Jafar; Warhade, Veenodini; Lohar, Deepak; Pinjara, Farukh Mohammad; Ansari, Adil Raza; Shrimali, Divyank; Purbia, Neha (Journal of Neonatal Surgery, 2025)
Knee osteoarthritis (KOA) is a major cause of disability in older adults, characterized by pain, joint stiffness, and reduced mobility. This study aimed to evaluate the effectiveness of Mat Pilates exercises on reducing pain and improving physical function in individuals with KOA. A total of 20 participants diagnosed with Grade 2 or 3 KOA were enrolled and received supervised Mat Pilates sessions combined with standard physiotherapy for four weeks, three times a week. Pain and function were assessed using the Visual Analog Scale (VAS) and the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC). The results revealed a statistically significant reduction in pain (mean VAS change: -2.35, p < 0.001) and improvement in functional capacity (mean WOMAC change: -7.45, p < 0.001). These findings suggest that Mat Pilates is an effective, low-impact intervention for managing symptoms and improving quality of life in KOA patients